Identification by force modulation microscopy of nanoparticles generated in vacuum arcs (2006)
This paper presents an alternative method based on force modulation microscopy (FMM), for the identification of nanogrobes produced in the plasma generated by the cathode spots of the arcs in a vacuum. The FMM technique is enabled for the detection of variations in the mechanical properties of a surface, with high sensitivity. Titanium nitride (TiN) coatings deposited on Silicon oriented by the pulsed arc process have been analyzed. Atomic force microscopy (AFM) and FMM microscopy images have been obtained simultaneously by means of which the presence of nanogotas has been identified. Additionally, X-ray diffraction spectra (XRD) have been taken from the coated samples. The existence of contaminating particles of 47 nanometers in diameter on the coatings has been reported.